Microbial succession during thermophilic digestion: the potential of Methanosarcina sp. - Paul Illmer; Christoph Reitschuler; Andreas Otto Wagner; Thomas Schwarzenauer; Philipp Lins (PLoS ONE)
A distinct succession from a hydrolytic to a hydrogeno- and acetotrophic community was well documented by DGGE (denaturing gradient gel electrophoresis) and dHPLC (denaturing high performance liquid chromatography), and confirmed by qPCR (quantitative PCR) measurements and DNA sequence analyses. We could prove that Methanosarcina thermophila has been the most important key player during the investigated anaerobic digestion process. This organism was able to terminate a stagnation phase, most probable caused by a decreased pH and accumulated acetic acid following an initial hydrolytic stage. The lack in Methanosarcina sp. could not be compensated by high numbers of Methanothermobacter sp. or Methanoculleus sp., which were predominant during the initial or during the stagnation phase of the fermentation, respectively.